ChemInform Abstract: Atroposelective Synthesis of Axially Chiral Biaryldiols via Organocatalytic Arylation of 2‐Naphthols. Issue 20 (April 2016) - Chen, Ye‐Hui; Cheng, Dao‐Juan; Zhang, Jian; Wang, Yong; Liu, Xin‐Yuan; Tan, Bin
Abstract: The scalable reaction of 2‐naphthols with quinone derivatives offers access to the title products in high yields and with very high enantioselectivities.